Kinetic Study of Biodiesel Purification from Used Cooking Oil Using Activated Carbon - Nurmawati, Ardika; Adi Saputro, Erwan; Latief, Masykuri; Mahendra, Iqbal; Saputro, Wiliandi (ASEAN Journal of Chemical Engineering, 2024)
Used cooking oil (UCO) is a hazardous pollutant that leads to environmental problems. In general, UCO was discharged directly into the water, although it has the potential to be processed. One alternative process of UCO is its potency as the main material of biodiesel production. Biodiesel is produced via a transesterification process, during which the reaction between UCO and alcohol occurs. The results obtained from this reaction include biodiesel and glycerol. In this study, pure biodiesel was obtained by purification using the adsorption process. The adsorbent was activated carbon from coconut shells that were contacted at a certain concentration and contact time. The adsorbent concentrations were varied from 3, 6, 9, and 12(w/w) addition, while the contact times were 30, 45, 60, 75, and 90 min. The crude biodiesel adsorption was carried out at 90oC. FFA removal increased with increasing adsorbent concentration and contact time. With 12% adsorbent addition, FFA was removed up to 64.91% in a 90 min adsorption process. The kinetics of the adsorption process were analyzed using several kinetics models, either in the linear or nonlinear form. The best kinetic fit in this process was obtained using a nonlinear pseudo-second-order model.